Antibacterial Effects of Leaf Extracts of Four Mangrove Plant Species on Staphylococcus aureus and Streptococcus pneumoniae - Thomas, Anu Susan; Koshy, Liji (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Antibiotic resistance is a significant global health concern, with bacteria developing resistance to commonly used antibiotics. Evaluating anti bacterial properties of natural extracts may offer alternative treatments to combat resistant bacterial strains. In this current investigation, the antibacterial activity of leaves of Avicennia marina, Avicennia officinalis, Bruguiera cylindrica and Rhizophora apiculata was evaluated against human pathogens such as Staphylococcus aureus and Streptococcus pneumoniae. Ethanol extracts of mature leaves of these mangrove plants were prepared and tested for antibacterial activity using agar disc diffusion method. Streptococcus aureus was inhibited by leaf extracts of A.marina, A.officinalis and B.cylindrica. In this study, the effectiveness of charcoal treated and charcoal untreated leaf extracts were also compared. Charcoal treated leaf extracts of Avicennia marina, Avicennia officinalis, Bruguiera cylindrica and Rhizophora apiculata were able to inhibit the growth of both tested pathogenic bacteria more than that of untreated leaf extracts. The leaf extract of Avicennia marina exhibited the highest antibacterial activity against S.pneumoniae and S.aureus compared to other extracts. The results suggested that these extracts offer enormous promise for producing novel antibiotics and could be used as an alternative source for treatment of infections caused by these tested pathogenic bacteria.